Effectiveness of Mandatory Labor Report in Company of Network for Provision of Company Data - Jamaludin Al Ashari; Arpangi Arpangi (Law Development Journal, 2021)
This study aims to determine and analyze the effectiveness of the application of compulsory employment reports in networks (online) in supporting the provision of company data in districts/cities, especially in Salatiga. The research method used in this writing is sociological juridical. Based on the research, it is concluded that the enforcement of mandatory employment reports in companies in the network (online), in terms of reporting speed, helps the government and entrepreneurs or company administrators to carry out their reporting obligations, but in terms of quantity and quality of reporting, it is considered ineffective in supporting the provision of company data in the City of Salatiga.